Study of Gas Permeability and Separation Behaviour for Removal of High Content C02 from CH4 by Using Membrane Modelling - Chin Han, Lim (Universiti Teknologi Petronas, 2004)
The removal of C02 from natural gas down to the pipeline quality is an important step before the natural gas can be sold to the end users. Typical natural gas treatment's specification requires that the composition of C02 in the treated gas cannot be more than 2 mole%. Currently, amine scrubbing units like Benfield process is extensively used to treat low content of C02 in the natural gas. For high concentration of C02 in the natural gas stream, the use of amine unit is economically restricted, as the recirculation rate needs to be increased to cater the need. The use of membrane separator to treat high content C02 natural gas has matured over the years and is said to work best at high C02 inlet partial pressure, as this results in increased permeation of the acid gas across the membrane. However, in the meantime to achieve low sale gas specification, the natural gas recovery in a membrane separator remains a question that needs to be explored. This modelling work comprises the study of gas permeability of pure C02 and CI-4 and the separation behaviour of C02 I CI-4 mixture under different process influences. The purpose is to predict the capability of membrane separator in separating high content C02 in the natural gas by using mathematical modelling. Data for y -alumina and acetate cellulose membranes, as cited from various references were used in this modelling work. The accuracy of the models developed, which incorporates the main transport mechanisms due to viscous, Knudsen and surface diffusion, was tested using experimental data cited. Simulation results show that the permeability of C02 and CH4 depend strongly on the pore size of the membrane, temperature and feed composition of the mixture. The effect of pressure on gas permeability is only apparent at small pore size. It was found that surface diffusion predominates the other transport mechanisms at small pores, and it poses the most selective transport mechanism to separate the C~ from CH4. However, when the pore size increases, surface diffusion starts to lose its effect as the gas molecules continue to diffuse via Knudsen diffusion mechanism. The results showed that Knudsen diffusion eventually increases the permeability of the gas molecules, but sacrifice in term of separation selectivity was observed at higher pore size. The contribution of viscous diffusion is not apparent as overall. The permeability of pure gas is inversely proportional to the system temperature, and directly proportional to the operating pressure at small pores only. The variation of surface diffusion due to the effects of both pressure and temperature is profound at small pore regions. The permeability of C02 and C~ in C02 I C~ mixture will approach the pure gas permeability as their feed composition increases. The investigation of separation behaviour of this binary system revealed that the performance of the single - stage alumina membrane separator is constant over a range of possible operating pressures. However, the separation factor decreases when the temperature increases. It showed that the separation factor of this binary system can be enhanced to be maximum at temperature near 80°C for separation that takes place in small pore region of the r -alumina membrane used. The separation factor is also a strong function of both the feed composition of C02 and the separation stage cut. Membrane separator becomes more efficient in term of selectivity and removal efficiency at high feed composition of C02 and higher stage cut. The high stage cut used to obtain sharp separation, however decreases the attractiveness of this binary separation due to increased loss of natural gas to the impurities stream.